2023
DOI: 10.1093/jncics/pkad079
|View full text |Cite
|
Sign up to set email alerts
|

Using existing pediatric cancer data from the Gabriella Miller Kids First Data Resource Program

Alexandra Hudson,
Marcia Fournier,
James Coulombe
et al.

Abstract: Childhood cancer and birth defects (BDs) are leading causes of childhood mortality, and studies suggest that BDs increase pediatric cancer risk. The Gabriella Miller Kids First Pediatric Research Program (Kids First) seeks to alleviate these conditions by building an expansive resource of genetic and clinical data from pediatric cancer and BD patients and families. This article describes the data and support provided by the Kids First Data Resource Center (DRC) and the Kids First Portal, which allows the publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…41 While RNA from normal tissue was not available from cases, a subset of neuroblastoma tumors from GMKF patients (N=89/688) had previously undergone transcriptome profiling, allowing us to assess the effect of SVs on tumor expression. 28 To assess the overall impact of singleton SVs on genes with varied degrees of expression, we converted gene expression values to a sample-normalized percentile rank (0-1) across all 89 samples and assessed the average rank of samples with SVs. We found that singleton SVs tended to decrease expression of their affected genes in the patients’ corresponding tumor, a result that was significant for two categories (e.g., singleton SVs affecting genes expressed in adrenal tissue rank mean=0.35 vs. 0.50 uniform null, P=0.03, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…41 While RNA from normal tissue was not available from cases, a subset of neuroblastoma tumors from GMKF patients (N=89/688) had previously undergone transcriptome profiling, allowing us to assess the effect of SVs on tumor expression. 28 To assess the overall impact of singleton SVs on genes with varied degrees of expression, we converted gene expression values to a sample-normalized percentile rank (0-1) across all 89 samples and assessed the average rank of samples with SVs. We found that singleton SVs tended to decrease expression of their affected genes in the patients’ corresponding tumor, a result that was significant for two categories (e.g., singleton SVs affecting genes expressed in adrenal tissue rank mean=0.35 vs. 0.50 uniform null, P=0.03, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Effectively all (99%) pediatric cancer cases were sequenced by the Gabriella Miller Kids First Pediatric Research Program (GMKF) or St. Jude Children's Research Hospital. [25][26][27][28][29] We combined these cases with ancestry-matched adult controls sequenced by two cardiovascular disease studies: the Multiethnic Study of Atherosclerosis (MESA) and the Mt. Sinai BioMe Biobank (BioMe).…”
Section: Characterization Of Germline Svs In 9374 Genomesmentioning
confidence: 99%
“…Cloud computing has long held the promise of facilitating large-scale bioinformatic analyses due to its ability to house and assess big data 1 . But as data expanded in the cloud, many available biomedical datasets were siloed and some were separated into distinct Data Coordinating Centers (DCCs), each with their own niche: GTEx for tissue-specific gene expression 2 , Gabriella Miller Kids First (GMKF) 3 for childhood cancer and structural birth defects, exRNA for extracellular RNA 4 , and many more. These data silos presented an interoperability bottleneck for analyses in the cloud 5 .…”
Section: Introductionmentioning
confidence: 99%